A method for optimizing sail design - Sugimoto, T. (Sports Engineering, 1999)
This study presents a method for optimizing sailing strategy, which also serves as sail optimization for maximum yacht speed. A concise mathematical model of up-wind sail mechanics is derived. This model is based on conventional wing theory, and it accounts for effects due to heel. In the modelling process two control parameters, the reef and the flat, are defined rigorously. Numerical and/or experimental data can be easily incorporated in this formulation through aerodynamic coefficient estimation. With the present aerodynamic model and conventional hull hydrodynamics, yacht equilibrium can be described by a set of nonlinear equations in terms of yacht speed and control parameters. Hence the entire problem assumes the nonlinear optimization of up-wind sailing strategy. A model calculation has been made to optimize sailing strategy for a yacht having an optimum sail. The numerical example leads to the results: (i) used in light winds, the sample design is optimum; (ii) used in strong winds this sail needs redesign with the constraint on mast height; (iii) the reef is sensitive to wind strength while the flat is sensitive to wind direction.